Lovecake's Marketing Strategy Bengkulu City - Cecilia Sondang Aprilia; Oni Yulianti; Ida Ayu Made Er Meytha Gayatri (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is to see how Lovecake’s strategy of Bengkulu City and the fears, weaknesses, opportunities and threats that will occur in the future in increasing sales. This study used SWOT analysis method by selecting consumers who come as the respondents. LoveCake's was founded in 2016 located on Jalan Dempo Raya No.5 Kebun Tebeng. Based on the research sequence, the sample consisted of internal factors, namely 7 people who were the owners and employees of LoveCake's and external factors of 35 people who were the consumers. Based on the SWOT analysis, it is known that LoveCake’s of Bengkulu City has a strength value of 33.6, weaknesses of 4.19. Therefore, the IFAS complementary is 33.6 - 4.19 = 29.41 while the opportunity value is 20.91 and the threat is 8.19. Thereore, the EFAS quadrant is equal to 20.91 - 8.19 = 12.72. Then, it looks like LoveCake’s is at coordinates (29.41 - 12.91) in quadrant (1). This quadrant position is a very profitable position, a field that has opportunities can take full advantage of existing opportunities. LoveCake's is expected to implement a strategy that supports an aggressive growth policy.